Corpus based study of verby explain and clarify as an example of assistance in pedagogical settings - Séguin, Maja (ExELL, 2025)
The use of synonymy and near-synonymy allows us to differently express similar ideas and meanings, as well as perspectives. However, their use and nuances may be unclear to language learners, such as the selected case of the verbs explain and clarify. This paper examines the usage of the two verbs by looking into corpus data and uses Sinclair’s methodological procedure as an alternative to dictionary references. Also included is a discussion of aspects and criticisms of corpus linguistics, mentions (and uses of) computer technologies for the analysis of language by discovering usage patterns, significant exceptions and semantic prosody, and exploring whether using corpora in the classroom would be beneficial to language learners.